2019
DOI: 10.1111/dmcn.14387
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of depression symptoms in children with epilepsy

Abstract: Aim To examine self‐ and proxy‐reported symptoms of depression in children with epilepsy. Method This was a prospective longitudinal cohort study of children with epilepsy. Participants were treated at six Canadian tertiary‐care centers and followed over 28 months with repeated assessments of child self‐reported symptoms of depression using the Children’s Depression Inventory Short‐Form (CDI‐S). Trajectories of symptoms of depression were estimated using linear mixed effects (LME) modeling. Results At baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This finding echoes previous research that found strong correlations between focal seizures and comorbid psychiatric disorders, specifically depression 3 , 27 , 28 but there are dissent views. 29 The findings revealed that children ranging from 9–12 years reported more depressive symptoms and females experienced fewer symptoms of depression, however, the associations were insignificant. Our finding that the female gender has lower depressive symptoms appears to contradict previous studies where depressive symptoms are common in females in the general population as well as those with chronic conditions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This finding echoes previous research that found strong correlations between focal seizures and comorbid psychiatric disorders, specifically depression 3 , 27 , 28 but there are dissent views. 29 The findings revealed that children ranging from 9–12 years reported more depressive symptoms and females experienced fewer symptoms of depression, however, the associations were insignificant. Our finding that the female gender has lower depressive symptoms appears to contradict previous studies where depressive symptoms are common in females in the general population as well as those with chronic conditions.…”
Section: Discussionmentioning
confidence: 90%
“… 23 , 24 A prospective longitudinal cohort study of CWE at six Canadian tertiary care centers followed children for over 28 months with repeated assessments using the Children’s Depression Inventory Short-Form. 25 The picture that emerged was stark; depressive symptoms remained persistent and pervasive and independent of age, types, and severity of the seizure. Although there is no study on the outcome of resective surgery among CWE, at least in the adult population, resective surgery initially appears to have kick started improvement in depressive symptoms, the improvement after resective surgery was more robust among those with superior seizure control.…”
Section: Discussionmentioning
confidence: 99%
“…The CDI‐2 is a self‐report questionnaire for children and adolescents designed to identify symptoms of depression appropriate for developmental age 55,61 . The CDI‐2 instrument has been utilized extensively in the pediatric epilepsy population 62,63 . The children with seizures completed this measure at B, M18, and M36.…”
Section: Methodsmentioning
confidence: 99%
“…55,61 The CDI-2 instrument has been utilized extensively in the pediatric epilepsy population. 62,63 The children with seizures completed this measure at B, M18, and M36.…”
Section: Children's Depression Inventorymentioning
confidence: 99%
“…Rosic and colleagues do us a great service by taking on this subject, not only in assessing depression, but by doing it repeatedly for 28 months . The sample itself is impressive: 336 children and adolescents completed the study, although the group appeared to be largely heterogeneous.…”
mentioning
confidence: 99%